2012
DOI: 10.1089/neu.2011.2106
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Forelimb Function after Unilateral Cervical Spinal Cord Injury: Novel Forelimb Tasks Predict Lesion Severity and Recovery

Abstract: Cervical spinal cord injury (cSCI) can cause devastating neurological deficits, including impairment or loss of upper limb and hand function. Recently there has been increasing interest in cervical spinal cord injury models because the majority of spinal cord injuries are at cervical levels. Here we examined spontaneous functional recovery of adult rats with either laminectomy or lateral hemisection of the cervical spinal cord at C3-C4. Behavioral tests were carried out, including the forelimb locomotor scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 46 publications
2
39
0
Order By: Relevance
“…Tests include the skilled paw-reaching staircase task [44][45][46] , pasta handling [47] , single-pellet retrieval [48,49] , ladder walking [50,51] , skilled walking and swimming [52,53] .…”
Section: Discussion and Perspectivementioning
confidence: 99%
“…Tests include the skilled paw-reaching staircase task [44][45][46] , pasta handling [47] , single-pellet retrieval [48,49] , ladder walking [50,51] , skilled walking and swimming [52,53] .…”
Section: Discussion and Perspectivementioning
confidence: 99%
“…Animals within a study group should be approximately the same weight, size and age as large differences in body weight can result in variation in the baseline distance needed for maintaining center of gravity for a given animal 19 . A sham group should be included while using PIT to verify that changes in behavior are due to regeneration or recovery rather than age and weight gain.…”
Section: Postural Instability Testmentioning
confidence: 99%
“…The postural instability test (PIT) was previously described and used in animals with a rodent model of Parkinson's disease 18 and in a rodent model of cSCI 19 . We used PIT after cSCI and found that there was a significant effect of lesion status [F(1,1) = 8.17, p < 0.01].…”
Section: Postural Instability Testmentioning
confidence: 99%
See 2 more Smart Citations